Risk Factors for COVID-19 Infection in Rural Areas: A Cross-Sectional Study in Tegal District - Siti Putri Nur Kholifah; Mahalul Azam; Muhamad Zakki Saefurrohim (Journal of Epidemiology and Public Health, 2021)
Background: Although the COVID-19 outbreak initially occurred in urban residents, it eventually reached rural and remote communities. There have not been many studies of risk factors for COVID-19 infection in people in rural areas. This study aimed to determine the factors associated with the incidence of COVID-19 infection in rural areas, Tegal Regency.Subjects dan Method: This was a cross-sectional study, conducted on 114 patients who visited the health center from 1 June to 30 July 2020 (time restrictions on social activities). The depen